Between history & poetry : the letters of H.D. & Norman Holmes Pearson - H. D. (Hilda Doolittle), 1886-1961 (University of Iowa Press, 1997)
In 1937 William Rose Benet sent a young Yale graduate student, Norman Holmes Pearson, to interview the sophisticated expatriate poet Hilda Doolittle during one of the few trips she made to America after going abroad in 1911. Until her death in 1961, they engaged in a prolonged and wide-ranging relationship vital to H.D.'s development as a writer. Perhaps because she was absent from the American scene, H.D. was eager for more contact with American writing, and Pearson became her literary adviser, agent, executor, confidant, close friend, and self-styled ""chevalier"". This annotated selection o